(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India, juvenile delinquency is a depressing reality. Over the last decade, the rate of juvenile offenses perpetrated by older teenagers aged 16 to 18 in India has risen considerably. These juveniles have recently been charged with some of the most terrible crimes, including murder and gang rape. This troubling rise of adolescent delinquency is a societal problem. The majority of Juvenile crime in recent years have been sexual offenses. To combat it, the new JJCPC ACT, 2015 states that 16- to 18-year-olds who commit a heinous crime may be tried as adults in specific circumstances, regardless of when they were arrested. The researchers are aiming to ascertain whether there has been an increase in heinous crime among older minors aged 16 to 18 in both India and Odisha.